2019
DOI: 10.1021/acs.joc.9b01385
|View full text |Cite
|
Sign up to set email alerts
|

Diversity-Oriented Synthesis of Imidazo-Dipyridines with Anticancer Activity via the Groebke–Blackburn–Bienaymé and TBAB-Mediated Cascade Reaction in One Pot

Abstract: A facile and metal-free one-pot protocol for the synthesis of fused imidazopyridine scaffolds has been developed. This novel protocol combines the Groebke–Blackburn–Bienaymé reaction (GBBR) with a sequential TBAB-mediated cyclization cascade. Biological evaluation demonstrated that compound 6a inhibits human prostate cancer cell DU-145 proliferation with an IC50 of 1.6 μM. The molecular mechanism study indicates that 6a significantly suppresses the oncogenic Erk kinase phosphorylation at 3 μM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Our results agree with those of Bu and collaborators [ 78 ], who reported that the imidazopyridine derivatives showed an antiproliferative potency against diffuse large B-cell lymphoma cells by the inhibition of mitogen-activated protein kinase (MAPK). In this regard, Li and collaborators [ 79 ] demonstrated that the molecular mechanism of anticancer activity of imidazopyridines involves a significant suppression of the oncogenic MEK/ERK kinase phosphorylation in human prostate cancer cells. In summary, imidazopyridines with ERK inhibiting effect may have a potential therapeutic benefit for cancer treatment, and our study is the first to show ERK 1/2 inhibition by a selenylated imidazo[1,2- a ]pyridine derivative in human glioblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our results agree with those of Bu and collaborators [ 78 ], who reported that the imidazopyridine derivatives showed an antiproliferative potency against diffuse large B-cell lymphoma cells by the inhibition of mitogen-activated protein kinase (MAPK). In this regard, Li and collaborators [ 79 ] demonstrated that the molecular mechanism of anticancer activity of imidazopyridines involves a significant suppression of the oncogenic MEK/ERK kinase phosphorylation in human prostate cancer cells. In summary, imidazopyridines with ERK inhibiting effect may have a potential therapeutic benefit for cancer treatment, and our study is the first to show ERK 1/2 inhibition by a selenylated imidazo[1,2- a ]pyridine derivative in human glioblastoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al 7 and Zhang et al 29 also reported on the utility of some imidazo[1,2-a]pyridin-3-amines as precursors for the synthesis of imidazo[1,2-a:5,4-b']dipyridines.…”
Section: Synthesismentioning
confidence: 99%
“…4,5 Moreover, N-fused polyheterocycles display also a wide range of biological activities. 6 In particular, imidazo[1,2-a:5,4-b']dipyridines exhibit interesting anticancer 7 and antiviral 8 activities. Some examples of biologically active compounds containing an imidazo[1,2-a:5,4-b']dipyridine such as (CF02334) 1, a selective inhibitor of the cytopathic effect (CPE) caused by bovine viral diarrhea 8 and anti-human prostate cancer 2 7 are outlined in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 In MCRs, three or more reactants are added in a single vessel and produce the target product, usually with acceptable efficiency. 13 These reactions are facile, fast, convergent, economic, and environmentally friendly with minimal waste generation, high yields, and no use of extra chemical solvents. 14,15 One of the important classes of MCRs used for the one-pot synthesis of the fused imidazoles is Groebke-Blackburn-Bienaymé reaction (GBBR).…”
Section: Introductionmentioning
confidence: 99%